Peningkatan Pengetahuan Continuity of Care pada Bidan untuk Cegah AKI-AKB & Stunting - Andriyanti, Andriyanti; Izzati, Dwi; Ningtyas, Woro Setia; Sabilillah, Nabilah (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
Stunting is one of the indicators to determine the quality of health services.. A strategic effort to overcome this is by implementing Midwife Continuity of Care (CoC) on the 1000 HPK (First Day of Life) by midwives. Probolinggo Regency has the 5th highest mortality rate in East Java Province with an MMR of 201 per 100,000 live births in 2022, while the IMR rate reaches 10.4 per 1,000 live births. One of the factors that influences this problem is the midwife's lack of knowledge regarding CoC care. Research shows that implementing CoC can significantly reduce the risk of maternal and neonatal complications. The aim of this community service activity is to increase midwives' knowledge regarding Continuity of Care. Methods include module development, training, and interactive discussions. The first stage is creating a CoC guide module for midwives and a parenting guide for parents. The second stage involves training for midwives and cadres on the concepts and implementation of CoC. Additionally, the activity is conducted in the form of interactive discussions and reflections on the CoC practices carried out by the midwives and cadres. The final stage is the ASAH (Asih, Asah, and Asuh) class for mothers with infants and toddlers, aimed at enhancing their knowledge in monitoring child growth and development. The results of this activity show an increase in midwives' knowledge of 21% after participating in training and simulations. The midwives involved also showed a commitment to implementing CoC in daily services, with the hope of contributing to improving the quality of sustainable midwifery services in their area. This program is expected to be an important step in and accelerate efforts to prevent MMR, IMR and Stunting in Indonesia